2021
DOI: 10.3389/fphy.2021.709151
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Pulse Driving Waveform With Rising Gradient for Improving the Aperture Ratio of Electrowetting Displays

Abstract: As a reflective display technology, electrowetting displays (EWDs) have the advantages of paper-like display, low power consumption, fast response, and full color, but the aperture ratio of EWDs is seriously affected by oil dispersion and charge trapping. In order to improve the aperture ratio and optimize the display performance of EWDs, a combined pulse driving waveform with rising gradient design was proposed. First, an initial driving voltage was established by the threshold voltage of oil film rupture (Vt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…When the driving voltage exceeds the threshold voltage, the oil film ruptures at its thinnest part. The Coatings 2023, 13, 935 4 of 14 ruptured oil film shrinks along the pixel wall, and the surface area of the shrunken oil film can be calculated using Equation (4) [36]:…”
Section: Oil Film Splittingmentioning
confidence: 99%
“…When the driving voltage exceeds the threshold voltage, the oil film ruptures at its thinnest part. The Coatings 2023, 13, 935 4 of 14 ruptured oil film shrinks along the pixel wall, and the surface area of the shrunken oil film can be calculated using Equation (4) [36]:…”
Section: Oil Film Splittingmentioning
confidence: 99%
“…As shown in Figure 12a, four different driving waveforms were used to compare performance with the proposed driving waveform. The four driving waveforms include a combined pulse waveform [20], an exponential function waveform with a reset stage [32], a linear function waveform [19], and an exponential function waveform [33]. In order to control the variable, the duration of the oil shrinking stage in all driving waveforms was set to 180 ms, and the maximum driving voltage V max was set to 30 V. The initial voltage of both the linear function waveform and the exponential function waveform with a reset signal was set to 16 V. luminance oscillations, which could not maintain a stable luminance value.…”
Section: Performance Of the Proposed Waveformmentioning
confidence: 99%
“…However, the response time of EWDs was correspondingly increased. In order to solve this problem, a combined pulse driving waveform was proposed [20]. During the rising stage, the voltage was driven from the threshold voltage to a maximum voltage, which effectively shorten the response time.…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al studied the optoelectronic performance of ink contact angles by deriving pixel hydrodynamic behavior from a Maxwell stress tensor and the flow phase field of the water-oil layer [5]. Using an electrochemical point of view, Rivas et al, found that the degree of contact angle deformation could be controlled by increasing the solvation energy difference, in order to suppress the contact angle saturation phenomenon under an applied electric field [6]- [11]. Under the electrostatic force characteristics of capillary electric fluid of ink droplets, the charge on the three-phase contact wire constantly accumulates to produce a certain electrostatic force, which makes the capillary tension change, thus changing the contact Angle of the ink and leading to the hysteresis of the contact Angle [12]- [16].…”
Section: Introductionmentioning
confidence: 99%